Mansfield Park. - Giles, David, 1926-2010; Willingale, Betty; Austen, Jane, 1775-1817 (Academic Video Online, 1983)
Fanny has grown up to be an indispensable member of the household at Mansfield Park. During Sir Thomas's absence abroad, the glam Crawfords arrive to stay in the neighbourhood.